Analysis of the effectiveness of coupon-mediated newborn hearing screening program through comparison of two government-funded pilot projects in South Korea. (September 2020) - Park, Su-Kyoung; Chang, Jiwon; Chung, You Sun; Oh, Seung-Ha
Abstract: Objective: The aims of this study are to compare the results of two government-funded newborn hearing screening (NHS) pilot programs and evaluate the feasibility and the effectiveness of the coupon-mediated NHS program in Korea. Methods: We retrospectively analyzed the database of the NHS center of the Ministry of Health and Welfare (MHW) from 2007 to 2013. Before the NHS was covered by national health insurance in 2018, the MHW conducted two types of NHS pilot programs. For the first pilot program, the MHW initiated an area based universal newborn hearing screening (UNHS) program which initially included 16 in 2007 and then spreading to 32 administrative areas in 2008 for all newborns in the pilot areas regardless of income level. The second pilot program was an offshoot of the continuing expansion of the first pilot program, which was a nationwide coupon-mediated NHS program for low-income families from 2009. The hearing loss (HL) was defined as a threshold of 40 dB nHL or worse on the auditory brainstem response (ABR) test. In both NHS pilot programs, the government financially supported the cost of the first NHS test and one ABR test for an infant who did not pass NHS test. Results: During the 1st NHS pilot program, 29.8% of the target neonates were screened which was 3.9% of total births; during the 2nd NHS pilot program 81.1% of the target neonates were screened which was 8.8% of total births. Documented diagnostic ABR tests were performed in 12.4% of referred infants in the 1st program and 33.5% in the 2nd program. The prevalence of HL was 0.11% in the 1st program and 0.15% in the 2nd program. In the 2nd NHS coupon-mediated program, the NHS was performed on average 5.4 ± 8.7 days after birth, and the diagnostic ABR test in the referred infants were performed on 61.3 ± 45.0 days after birth. There was no comparable recorded data in the 1st NHS pilot program. Conclusions: This study suggests that the coupon-mediated NHS pilot program may be a worthwhile government-led NHS project for the proper tracking and accurate statistics. This program helped formulate UNHS national health insurance policies. However, to become a successful UNHS program, the governmental supports for both timely interventions and the inauguration of a web tracking system are mandatory.